The Use Of Reels Instagram To Facilitate The Secondary School Students’ Speaking Skills - Yuli Ristianti; Dessy Dwi Yudha Santhi; Juhana Juhana (Dinasti Publisher, 2025)
Effective speaking is an essential communication component, serving as the foremost expression of language. It holds considerable importance in multiple facets of life, and proficient speaking necessitates practice in mechanics, functions, and social and cultural conventions. This study explores the used of Instagram's new feature, Reels, to improve speaking fluency among students. Reels feature on Instagram offers a new approach to teaching, allowing students to feel more confident and creative to enhance their speaking skills. This qualitative study involved 25 seventh-grade students from one of private schools in Bandung, West Java, Indonesia. The data were obtained through observations, questionnaires, and interviews. The analysis was done by applying the data condensation, data display, and conclusion drawing. The results showed that most students accomplished their projects effectively, demonstrating enthusiasm and active engagement. The findings showed that implementing Reels in the speaking project improved the students’ speaking skills. It also enhanced their self-confidence, social skills, and proficiency in other language skills, specifically Bahasa Indonesia. This study also revealed that students faced challenges in the Reels speaking project, including internet connectivity, pronunciation, and video-making. However, they successfully navigated these issues. Despite challenges, integrating technology into education promotes a positive learning environment and enhances students' communication and language abilities.